2004
DOI: 10.1111/j.1368-5031.2004.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Computerised tomography vs. pathological staging of laryngeal cancer: a 6-year completed audit cycle

Abstract: The aim of this audit was to examine the accuracy of computerised tomography (CT) staging of advanced laryngeal tumours. CT staging was evaluated against the T staging of laryngeal tumours as determined by pathological examination. Data from 38 patients, between 1996 and 2000 with laryngeal squamous cell cancer that fulfilled the audit criteria, were collected and compared. Subjects had to have a pre-operative CT scan of the larynx and a total laryngectomy specimen for pathological staging. The audit demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 4 publications
2
15
0
3
Order By: Relevance
“…All clinical/endoscopic staging errors occured from underestimation caused by a failure to clinically identify invasion of the paraglottic and preepiglottic space and laryngeal cartilaginous structures. Agada et al reported the accuracy of CT staging compared with pathologic specimens, demonstrating that 45% of patients were overstaged and 10% were understaged by CT (24). In our study, overestimation of stage was present in 14.2 % of cases and underestimation in 3 %.…”
Section: Discussionmentioning
confidence: 54%
“…All clinical/endoscopic staging errors occured from underestimation caused by a failure to clinically identify invasion of the paraglottic and preepiglottic space and laryngeal cartilaginous structures. Agada et al reported the accuracy of CT staging compared with pathologic specimens, demonstrating that 45% of patients were overstaged and 10% were understaged by CT (24). In our study, overestimation of stage was present in 14.2 % of cases and underestimation in 3 %.…”
Section: Discussionmentioning
confidence: 54%
“…5 Agada et al 6 reported the accuracy of CT staging compared with pathologic specimens, demonstrating that 45% of patients were overstaged and 10% were understaged by CT. Other studies have examined the potential benefits of smaller sections, by using coronal/sagittal and 3D reconstructions and having patients do a variety of breathing maneuvers, including quiet breathing, breath-holding, and modified Valsalva maneuvers. 7 Results in these studies varied, but most found that reconstructions are helpful and that breathing maneuvers improve imaging quality.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other radiologic signs used to predict early cartilage invasion include cartilage sclerosis, intramedullary cartilaginous mass, cartilaginous explosion, cartilage lysis, and cartilage bowing. [14][15][16][17] Sclerotic changes in the laryngeal cartilage as a result of tumoral involvement are controversial. The ability of CT to detect neoplastic invasion of laryngeal cartilage varies widely, with reported sensitivities of 46%-66% and specificities of 84%-94%.…”
Section: Discussionmentioning
confidence: 99%